Use Best Practices to Avert Water Treatment Complacency. Issue 6 (1st June 2015) - Martin, Barb; Barsotti, Michael
Abstract : Drought, wildfires, storms, and other potentially serious events can significantly impact source water quality. Water treatment plant staff must be especially vigilant and prepared to maintain effective water treatment and treated water quality during such occurrences.